2020
DOI: 10.3390/biom10121614
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia as a Driving Force of Pluripotent Stem Cell Reprogramming and Differentiation to Endothelial Cells

Abstract: Inadequate supply of oxygen (O2) is a hallmark of many diseases, in particular those related to the cardiovascular system. On the other hand, tissue hypoxia is an important factor regulating (normal) embryogenesis and differentiation of stem cells at the early stages of embryonic development. In culture, hypoxic conditions may facilitate the derivation of embryonic stem cells (ESCs) and the generation of induced pluripotent stem cells (iPSCs), which may serve as a valuable tool for disease modeling. Endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 139 publications
1
33
0
Order By: Relevance
“…Early stages of embryonic growth are hastened by reduced oxygen tension. 7 This was the basis of shifting to culturing embryos in reduced oxygen pressure. Increased production of ROS are blamed to cause decreased fertilization rate, reduced cleavage rate and reduced blastulation.…”
Section: Discussionmentioning
confidence: 99%
“…Early stages of embryonic growth are hastened by reduced oxygen tension. 7 This was the basis of shifting to culturing embryos in reduced oxygen pressure. Increased production of ROS are blamed to cause decreased fertilization rate, reduced cleavage rate and reduced blastulation.…”
Section: Discussionmentioning
confidence: 99%
“…This means that the preimplemented embryo is adapted to a low oxygen atmosphere. In humans, it has been shown that low oxygen atmospheres can produce high-quality embryos and improve implementation from developing zygotes [181]. Additionally, placental development is associated with hypoxia, as cytotrophoblasts, which are stem cells forming placenta, proliferate better at low oxygen concentrations in vitro [182,183].…”
Section: Hypoxia and Stem Cell Capacitymentioning
confidence: 99%
“…MYC, OCT4, SOX2 and NANOG are upregulated by HIF2a in these conditions, promoting pluripotency. Additionally, it has been shown that HIF2a can increase glycolytic flux under 5% oxygen, upregulating CTBP1 and CTBP2 to promote self-renewal [181].…”
Section: Hypoxia and Stem Cell Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of evidence suggests that low oxygen concentration, in combination with appropriate differentiation stimuli, promotes hiPSC differentiation into cells of mesodermal origin, such as endothelial cells, CMs, or chondrocytes [105,[113][114][115]. The effect of low oxygen tension on the endothelial differentiation potential of hPSCs was extensively reviewed in a recent paper by Podkalicka et al [116]. Briefly, the available data indicated that endothelial specification is enhanced under hypoxia.…”
Section: Mesoderm Differentiationmentioning
confidence: 99%